Godność małżeństwa - Kowal, Janusz (Horyzonty Wychowania, 2017)
In spite of the very difficult and complex situation of marriageand family in contemporary world, its negative image appearsvery one-sided, because there are also positive aspects of thissituation. The changes which have taken place and are presentin contemporary world point to a more distinctly genuine andpositive character of the institution of marriage.One of the areas where these changes have occurred morebroadly include the widespread model of monogamous marriageand conjugal laws which take into consideration the equality ofwomen’s rights and the freedom of choice of the spouse. EvenMuslim countries have experienced these changes; e.g. some ofthem introduced in the last century such marital regulations,which are all the more in conformity with the natural and evangelicalvalues of the institution of marriage and the dignity of thehuman person.The changes in contemporary world are also reflected in thecurrent legislation of the Catholic Church. Some newer norms protect, better than their predecessor did, the freedom of the parties contracting marriage and assure great protection against deceit or a conditioned act of the will for marriage. These examples bear witness to an ever greater esteem for the institution of marriage itself, as well as to the protection of the dignity of the persons who get married. The norms concerning the consummation of marriage and individual regulations showing „the favour of law” which marriage enjoys in the Catholic Church bear similar witness.